RELATIONSHIP BETWEEN WIDAL TITER WITH C-REACTIVE PROTEIN (CRP) LEVELS AND SEGMENTED NEUTROPHIL PERCENTAGE IN CHILDREN WITH TYPHOID FEVER AT GRAHA MEDIKA MARTAPURA CLINIC, BANJAR DISTRICT - Eka Wahyuni; Puspawati; Muhammad Arsyad; Syihab Fayumi (PT. Radja Intercontinental Publishing, 2026)
Typhoid fever is an infectious disease that remains a public health problem in Indonesia, particularly among children. Infection with Salmonella typhi can trigger an inflammatory response characterized by elevated C-reactive protein (CRP) levels and changes in the percentage of segmented neutrophils. The Widal test is still widely used to aid in the diagnosis of typhoid fever because it is simple, rapid, and cost-effective. This study aimed to determine the relationship between Widal titers and CRP levels and the percentage of segmented neutrophils in pediatric typhoid fever patients at the Graha Medika Martapura Clinic, Banjar Regency. This study employed an observational analytical method with a cross-sectional design. The data used were secondary data from the medical records of pediatric typhoid fever patients from January 2025 to March 2026. The study sample consisted of 206 patients selected using total sampling. Data analysis was performed using the Spearman rank correlation test. The results showed that the majority of patients had a Widal titer of 1/640 (65.5%), elevated CRP levels (59.7%), and a normal percentage of segmented neutrophils (84.5%). The correlation test results showed no significant association between the Widal titer and CRP levels (r=0.073; p=0.296) or the percentage of segmented neutrophils (r=0.064; p=0.361). It was concluded that the Widal titer is not associated with CRP levels or the percentage of segmented neutrophils in pediatric patients with typhoid fever.